High Sensitive and Non-invasive ctDNAs Sequencing Facilitate Clinical Diagnosis And Clinical Guidance of Non-small Cell Lung Cancer Patient: A Time Course Study - Li, Yongqiang; Lv, Jiajia; Wan, Shaogui; Xin, Junfang; Xie, Tiantian; Li, Tao; Zhu, Wan; Zhang, Guosen; Wang, Yunlong; Tang, Yitai; Li, Ao; Guo, Xiangqian (Frontiers in Oncology, 2018)
Abstract: Lung cancer is one of leading causes of cancer death all over the world. Non-small cell lung cancer (NSCLC) is the most predominant subtype of lung cancer. Molecular targeting therapy has been shown great success in the treatment of advanced NSCLC. Thus, an easy, sensitive and specific way of recognizing therapeutic gene targets would help to select effective treatments, to improve physical condition and increase patient survival. In this study, we recruited and followed up a female NSCLC patient, whose plasma ctDNAs (circulating tumor DNAs), blood cell DNAs, psDNAs (pleural effusion supernatant DNAs) and ppDNAs (pleural effusion pellet DNAs), were collected and analyzed over periodic time points by methods of next generation sequencing (NGS), droplet digital PCR (ddPCR) and Amplification Refractory Mutation System (ARMS). In addition, pleural effusion pellets were stained by IHC (immunohistochemistry). The investigation results showed that EGFR L858R mutation was recognized by methods of NGS, ddPCR and ARMS, while EGFR T790M mutation was only identified by methods of NGS and ddPCR but not ARMS, indicating that ARMS as an auxiliary clinical diagnostic method, is less sensitive and less reliable than NGS and ddPCR. In summary, the non-invasive and sensitive way of collecting ctDNAs for NGS and/or ddPCR screenings offers patients new diagnosis and therapeutic options.